Cultivating the Pancasila Student Profile in Early Childhood Using the Garuda Book: An Innovative Method in Indonesian Educational Practices - Masitah, Widya; Sitepu, Juli Maini; Raniyah, Qaulan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This study examines the effectiveness of the Garuda Book, a tailored educational tool for instilling the Pancasila Student Profile in early childhood education within Indonesia's Independent Curriculum framework. Utilizing a Research and Development (R&D) approach, this research involved creating, implementing, and evaluating the Garuda Book in an early childhood educational setting at RA Nurul Hadina. The study's methodology incorporated the development of project activities linked to the curriculum, including